2D lamellar membrane with nanochannels synthesized by bottom-up assembly approach for the superior photocatalytic hydrogen evolution. (October 2022) - Zhou, Weiming; Wu, Yiting; Huang, Hongqiang; Zhang, Mingxin; Sun, Xuhui; Wang, Zequn; Zhao, Fei; zhang, Houyu; Xie, Tengfeng; An, Meng; Wang, Liwei; Yuan, Zhanhui
Abstract: Designing nanoscale photocatalysts to improve photocatalytic efficiency is a popular research topic. However, for wide application and friendly environment, achieving good dispersion and multiple recycling of photocatalysts at the nanoscale remains challenging. Herein, a general bottom-up assembly method is proposed for designing a class of two-dimensional lamellar membranes (2DLMs) for photocatalytic applications. A bismuth oxychloride (BiOCl) nanosheet (BN) was used as a demo photocatalyst to construct a 2DLM via self-stacking. The designed BiOCl membrane (BM) exhibited excellent physical properties including flexibility, mechanical strength (tensile strength = 15.75 MPa, fracture strain = 0.056%), and translucence, as well as superior photocatalytic performance with excellent recycling stability and reusability. The photocatalytic hydrogen evolution performance of BM was 2.5-fold that of BN particles dispersed in an aqueous solution. Further theoretical calculations revealed that a BM with appropriately sized nanochannels can accelerate water transport, and the main horizontal channel size of the BM (3.13 nm) is very close to the size of the ideal water transport nanochannel. Furthermore, the confined internal space reduces the number of hydrogen bonds for water molecules within the nanochannels, thereby enhancing the interfacial reaction rate and photocatalytic efficiency. This study presents a simple bottom-up assembly method to design photocatalysts with further improved performance. Graphical abstract: Image 1 Highlights: A general strategy to design lamellar membrane (LM) for photocatalytic is proposed. The nanochannels speed up water transport and facilitate photocatalytic reaction. The hydrogen bonds among water molecules inside nanochannels are weakened. Photocatalytic H2 evolution activity of BiOCl LM is 2.5-fold that of its particles.